Perlindungan Hukum Bagi Pedagang Kaki Lima Dalam Berusaha Di Kota Madiun - Rezqi Nur Arifin (Terekam Jejak Publisher, 2024)
The aim of this research is to find out whether everyone, including those who do not live in Madiun City, can open a shop in a location and register a business selling food and drinks in public facilities or not and analyze the situation. Legal consequences if street vendors occupy a stall in a location that violates regional regulations in Madiun City. This research uses a type of normative legal research with a statutory approach and a conceptual approach. In analyzing the data, we use analysis and interpretation of legal construction to obtain a concise and clear picture to obtain practical answers for the problems discussed based on applicable laws and regulations. The research results show that residents who do not come from the Madiun City area cannot open a shop or apply for a business registration certificate. Any street vendor who violates regional regulations in Madiun City will be subject to administrative sanctions and have their business license revoked.